Prognostic value of myopic disk deformation in myopic choroidal neovascularization: A 6-year follow-up study - Han, Ye Eun; Kim, Yoon Jeon; Yang, Hyun Seung; Moon, Byung Gill; Lee, Joo Yong; Kim, June-Gone; Yoon, Young Hee (Frontiers in Medicine, 2022)
Purpose To evaluate the clinical characteristics of myopic choroidal neovascularization (mCNV) according to peripapillary atrophy (PPA) and optic disk tilt and to explore whether those myopic disk deformations are associated with the prognosis of mCNV. Methods Patients with subfoveal mCNV who received intravitreal bevacizumab injection and followed for ≥3 years were included. PPA was quantified as area of the ß-zone PPA/disk area ratio (PDR) and optic disk tilt as the tilt ratio (the longest/shortest disk diameter). We compared the clinical characteristics in terms of PDR and tilt ratio and identified the poor prognostic factors using Logistic regression and Cox proportional hazard model. Results Among 80 eyes of 80 patients, 29 (36.30%) eyes developed macular atrophy during 80.71 ± 34.76 months. PDR and tilt ratio are strongly correlated with each other (P = 0.004). Higher PDR showed significant correlations with longer axial length (P = 0.013), worse baseline and final VA (P = 0.007 and P = 0.047), and thinner subfoveal choroidal thickness (P = 0.039), while higher tilt ratio showed significant correlations only with longer axial length (P = 0.036). High PDR was also an independent risk factor for both macular atrophy (OR = 2.257, P < 0.001) and poor visual outcome (HR = 1.174, P = 0.007), while high disk tilt ratio was not. Conclusion Subfoveal mCNV with higher ß-zone PPA area/disk area ratio had worse functional and structural outcomes.